Primary education students’ scientific literacy in terms of some variables - Yuliana, Ivo; Jatmiko, Budi; Widodo, Wahono; Suryanti, Suryanti (Edelweiss Applied Science and Technology, 2025)
In numerous countries, including Indonesia, the primary objective of Primary Education has evolved to prioritize attaining scientific literacy. This study investigates the scientific literacy of pupils, examining variations by gender and grade level upon completion of science instruction. In this academic study, the coefficient sampling technique was employed to choose a cohort of 629 pupils from ten educations in the East Java province of Indonesia. The study methodology involved conducting a survey and gathering data by administrating the Scientific Literacy Test (SLT). The outputs of this study show that scientific literacy (SL) among Primary Education pupils is at a relatively low stage. Notable disparities in academic performance were studied based on gender and grade level. Interestingly, the commonly held social belief that men excel more than women in science did not appear applicable among the student population. Hence, it is imperative to conclude that before commencing Primary Education instruction, educators should assess the scientific literacy competencies of their pupils. A policy position about SL-in-action is developed and analyzed, considering the considerations that would confront decision-makers who shape the school’s primary curriculum policy.